307 A systems approach to understanding biosecurity decision-making. (30th November 2020) - Merrill, Scott C; Koliba, Christopher; Bucini, Gabriela; Clark, Eric; Trinity, Luke; Zia, Asim; Cheney, Nicholas; Langle, Ollin; Shrum, Trisha; Sellnow, Timothy; Sellnow, Deanna; Smith, Julia M
Abstract: Disease and its consequences result in social and economic impacts to the US animal livestock industry, ranging from losses in human capital to economic costs in excess of a billion dollars annually. Impacts would dramatically escalate if a devastating disease like Foot and Mouth Disease or African Swine Fever virus were to emerge in the United States. Investing in preventative biosecurity can reduce the likelihood of disease incursions and their negative impact on our livestock industry, yet uncertainty persists with regards to developing an effective biosecurity structure and culture. Here we show the implications of human behavior and decision making for biosecurity effectiveness, from the operational level to the owner/managerial level and finally to the systems level. For example, adjustments to risk messaging strategies could double worker compliance with biosecurity practices at the operational level. The improvement of our risk communication strategy may increase willingness to invest in biosecurity. Furthermore, the adaptation of policies could nudge behavior so that we observe a short disease outbreak followed by a quick eradication instead of a pandemic. Our research shows how the emergence of now-endemic diseases, such as Porcine Epidemic Diarrhea virus, cannot be adequately modeled without the use of a human behavioral component. Focusing solely on any one sector or level of the livestock system is not sufficient to predict emergent disease patterns and their social and economic impact on livestock industries. These results provide insight toward developing more effective risk mitigation strategies and ways to nudge behavior toward more disease resilient systems.